The peculiarities of motor fitness' classification model of 6-10 years old girls - O.V. Ivashchenko; S.S. Iermakov; O.M. Khudolii (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
The purpose of the research is determination of motor fitness' classification model of 6-10 years old girls. Material and methods: in the research 6 years old girls (n=36), 7 years old girls (n=48), 8 years old girls (n=57), 9 years old girls (n=38), 10 years old girls (n=46) participated. Testing program includes commonly known tests. Results: With age there happened some changes of coordination and power fitness, endurance, quickness, flexibility indicators. Suggested set of tests could be used for final control of girls' motor fitness. Conclusions: In the process of analysis was calculated canonic coefficients of discriminant function (not standardized). These coefficients are multipliers of the set values of variables, which are components of discriminants functions. On the basis of them it is possible to classify girls by the level of motor fitness according to their age.